Regarding the formation of the concept of critical infrastructure protection: the experience of the countries of the European Union and the USA - Kuznichenko, S. O.; Batiuk, O. V. (НДІ ПЗІР НАПрН України, 2023)
The need for a systematic approach to the protection of objects and resources critically important for the functioning of society and ensuring national safety is substantiated. The experience of the USA and the countries of the European Union regarding the protection of critical infrastructure is analyzed. The essence of the concept of "critical infrastructure" is considered. It is proposed to update the concept of critical infrastructure protection taking into account Industry 4.0 technologies. Необхідність систематичного підходу до захисту об'єктів та ресурсів, критично важливих для функціонування суспільства, та забезпечення обґрунтованості національної безпеки. Проаналізовано досвід США та країн Європейського Союзу щодо захисту критичної інфраструктури. Вважається суть концепції "критичної інфраструктури". Запропоновано оновити концепцію критичного захисту інфраструктури з урахуванням технологій галузі 4.0.
Keywords: critical infrastructure; protection of critical infrastructure; national safety; USA; European Union; Industry 4.0 technologies; критична інфраструктура; захист критичної інфраструктури; національна безпека; США; Європейський Союз; промисловість 4.0 технологій